PERLINDUNGAN HUKUM TERHADAP WAJIB PAJAK DALAM PENYELESAIAN SENGKETA PAJAK AIR PERMUKAAN DI SUMATERA UTARA STUDI KASUS PAJAK AIR PERMUKAAN PT INDONESIA ASAHAN ALUMINIUM (Persero) - DIAN LESTARI; Budiman Ginting; Sunarmi -; Sutiarnoto - (jurnal.unprimdn.ac.id, 2021)
PT INALUM (Persero) is in reality a BUMN. Differences in the application of Article 9 paragraph (3) of North Sumatra Governor Regulation no. 24 of 2011 with other BUMN will cause discrimination related to calculation of surface water tax. Based on this, PT INALUM (Persero) filed an objection to the Provincial Government of North Sumatera on the SKPD issued and subsequently rejected through the Letter of Objection. The Letter of Objection Resistation, PT INALUM (Persero) filed an appeal to the Tax Court and is still in court process.